The Influence Of Community Paticipation, The Role Of Bpd And Village Government Accountability On The Quality Of Village Development Planning In Sambelia District, East Lombok District In 2025 - Apandi Prayoga; Ahmad Hidayat (JURNAL ECONOMINA, 2026)
Effective village development requires quality planning, but in practice, various obstacles are still encountered, such as low community participation, the suboptimal role of the Village Consultative Body (BPD), and weak village government accountability. This study aims to analyze the influence of community participation, the role of the BPD, and village government accountability on the quality of village development planning in Sambelia District, East Lombok Regency. The study used a quantitative approach with a causal associative research type. Data were collected through questionnaires, documentation, and observations of 55 respondents consisting of village officials, BPD members, and community members selected using proportionate stratified random sampling techniques. Data analysis was performed using multiple linear regression using SPSS. The results showed that community participation, the role of the BPD, and village government accountability partially and simultaneously had a positive and significant effect on the quality of village development planning. Village government accountability was the variable with the most dominant influence. In addition, the three variables together were able to explain 70.9% of the variation in the quality of village development planning. This study concludes that improving the quality of village development planning can be achieved through strengthening community participation, optimizing the function of the BPD, and increasing the accountability of the village government in order to realize more effective, transparent, and responsive village governance to community needs.